2004
DOI: 10.1111/j.1745-4522.2004.01143.x
|View full text |Cite
|
Sign up to set email alerts
|

Polyphenolics Extracts From Legume Seeds: Correlations Between Total Antioxidant Activity, Total Phenolics Content, Tannins Content and Astringency

Abstract: Extracts of polyphenolic compounds were obtained from seeds of faba bean, broad bean, adzuki bean, red bean, pea, red lentil and green lentil using 80% (v/v) acetone. The total antioxidant activity (TAA) of extracts was determined and their astringency (Sensation Astringency Indices – SAI) investigated using the sensory scaling method. The content of tannins in extracts was expressed as absorbance values at 500 and 550 nm after color developed with vanillin/HCl reagent and after n‐butanol‐HCl hydrolysis, respe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
101
2
4

Year Published

2007
2007
2018
2018

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 153 publications
(119 citation statements)
references
References 17 publications
(27 reference statements)
12
101
2
4
Order By: Relevance
“…In the case of leguminous seeds extracts, a statistically significant (P ≤ 0.01) correlation was determined for total phenolics versus total antioxidant activ- Figure 7. Correlations between the total phenolics content and observed antioxidant activity from the β-carotenelinoleate model system (A and B; in A correlation was calculated for 7 points, in B one point was omitted), antiradical activity against DPPH radical (C), and reducing power (D) ity (TAA) (Amarowicz et al 2004a). The strong correlation between the content of total phenolics and the reducing power was found in the extracts of selected plant species from the Canadian prairies as reported by Amarowicz et al (2004b).…”
Section: Resultsmentioning
confidence: 99%
“…In the case of leguminous seeds extracts, a statistically significant (P ≤ 0.01) correlation was determined for total phenolics versus total antioxidant activ- Figure 7. Correlations between the total phenolics content and observed antioxidant activity from the β-carotenelinoleate model system (A and B; in A correlation was calculated for 7 points, in B one point was omitted), antiradical activity against DPPH radical (C), and reducing power (D) ity (TAA) (Amarowicz et al 2004a). The strong correlation between the content of total phenolics and the reducing power was found in the extracts of selected plant species from the Canadian prairies as reported by Amarowicz et al (2004b).…”
Section: Resultsmentioning
confidence: 99%
“…and ABTS .1 , and antioxidant activity in a b-carotene-linoleate model system. For extracts prepared from leguminous seeds (i.e., faba bean, broad bean, adzuki bean, red bean, red lentil, and green lentil) statistically significant correlations were reported between total antioxidant activity and tannins content determined by both the vanillin method (P ,0.01) and after n-butanol/ HCl hydrolysis (P ,0.05) [6].…”
Section: Tannins: the New Natural Antioxidants?mentioning
confidence: 99%
“…Salunkhe et al [20] suggested that phenolic substances occur primarily in the seeds of certain pigmented cultivars of sorghum, millets and legumes. Condensed tannins, the predominant phenolic compounds in legumes seeds were widely found in lentil, pea, coloured soybean and common bean [21][22][23][24].…”
Section: Condensed Tannin Contentmentioning
confidence: 99%